2019
DOI: 10.1111/hsc.12795
|View full text |Cite
|
Sign up to set email alerts
|

The impact of adolescents' racial and ethnic self-identity on hope

Abstract: The two components of hope (i.e., hope‐agency defined as the ability to envision and believe in one's ability to achieve goals; hope‐pathway defined as belief in one's ability to devise strategies to achieve one's goals) propel adolescents toward well‐being, academic achievement and personal fulfillment. This study compares levels of hope and its components, for different groups of immigrant and ethnic non‐immigrant youths, while adjusting for and measuring the impact of racism, school and family characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 58 publications
(72 reference statements)
0
3
1
1
Order By: Relevance
“…Although the social identity literature has also shown that one's biology (eg, race or sex at birth) does not always align with one's social identity (eg, ethnic or gender identity), 4,23 we found a strong association between clinical epilepsy-related factors and SEI here. Patients who achieved a better seizure outcome, had a longer period of seizure freedom prior to taking part in the study, and were taking fewer ASMs were more likely to show explicit and implicit features of identifying as someone without epilepsy.…”
Section: Explicit Sei Mediates the Impact Of Seizure Outcome On Hrqolcontrasting
confidence: 53%
See 1 more Smart Citation
“…Although the social identity literature has also shown that one's biology (eg, race or sex at birth) does not always align with one's social identity (eg, ethnic or gender identity), 4,23 we found a strong association between clinical epilepsy-related factors and SEI here. Patients who achieved a better seizure outcome, had a longer period of seizure freedom prior to taking part in the study, and were taking fewer ASMs were more likely to show explicit and implicit features of identifying as someone without epilepsy.…”
Section: Explicit Sei Mediates the Impact Of Seizure Outcome On Hrqolcontrasting
confidence: 53%
“…Another facet of social identity that we can measure relates to a person's implicit attitudes and behaviors associated with group membership, such as joining peer support groups, participating in research, or advocating for supports and services for people with epilepsy. 4,5,23 To date, research on social identity in epilepsy has focused predominantly on the experience of stigma for people living with epilepsy and how this may vary across different cultures. 1,24 There is a dearth of research examining the nuances of social identity in people living with epilepsy, and to date no research into the long-term impact of surgery on social identity.…”
Section: Introductionmentioning
confidence: 99%
“…14 Thus, the agency reflects a person's motivation to succeed in goal achievement and thus could represent the emotional part of hope. 15 Meanwhile, well-being or wellness at work incorporates ones' satisfaction with the various personal life as well as work-life aspects. Over the last 3 decades, the well-being of nurses has been overwhelmed by stresses and challenges in their daily practice.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the theoretical links between hope and CC, only a handful of studies have empirically examined the relationships between hope and CC among marginalized youth. In one study conducted in Israel, Zlotnick et al (2019) found that youth who were Ethiopian immigrants, a group that comprise just 1% of the total population in Israel, had higher hope if they also had high awareness of discrimination and racism. This finding suggests that hope is related to an awareness of the ways one's group experiences disadvantages within society, and this relationship is examined in‐depth in the present study by considering longitudinal associations between hope and critical reflection.…”
Section: Literature Reviewmentioning
confidence: 99%